Argument-based science inquiry (ABSI) models to improved capability of scientific argumentation - Fitria Nurdianti; H Hernani; P Siahaan (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2020)
The purpose of this study was to developed argument-based science inquiry (ABSI) models to improved capability of scientific argumentation. The method used was Descriptive Research. The instruments of data collection used in this study were observation sheet, teachers structured questions, form of interview, scientific argumentation test. This study was conducted in junior high schools plus An-Naba Sukabumi with 25 seventh-grade students. The average results of students answers have the ability to argumentation at first level and only a few have the ability to argument at second level and one of the ways to improve student argumentation was experiment. One learning model that can be applied to improve students' argumentation is argument-based science inquiry (ABSI). The application of ABSI in enhancing the argumentation skills is in the research stage.